Evaluation of Short‐term Outcomes of Tracheostomy Procedures in a NICU Population With High Ventilator Settings. (9th March 2021) - Banks, Laura; Worobetz, Noah; Hamersley, Erin; Onwuka, Amanda; Shepherd, Edward; Wiet, Gregory
Abstract : Objective: To investigate whether tracheostomy placement in infants requiring high ventilator pressure is safe and effective. Study Design: Case series with chart review. Setting: Tertiary children's hospital. Methods: Fifty ventilator‐dependent neonatal intensive care unit patients who underwent tracheotomy from 2009 to 2018 were included. Patients requiring high ventilator pressures were compared to those requiring low ventilator pressures. Demographics, comorbidities, and surgical and clinical data were recorded. Results: Thirty‐two percent (n = 16) had low ventilator settings at the time of tracheostomy tube placement, and 68% (n = 34) had high ventilator settings. The median peak inspiratory pressure of the high ventilator group was 29.5 cm H2 O, positive end‐expiratory pressure (PEEP) was 8 cm H2 O, mean airway pressure was 13 cm H2 O, pressure support (PS) was 14 cm H2 O, PS above PEEP was 6 cm H2 O, and inspiratory time was 0.65 seconds. The high ventilator cohort had a higher median age at the time of surgery compared to the low ventilator group ( P =. 02). Female patients were more likely to have high ventilator settings ( P =. 02). There were no intraoperative complications or deaths within the first 7 days of tracheostomy tube placement. Pneumonia incidence and rate of mortality during admission did not vary by ventilator settings ( P =. 92 and P =. 94, respectively). Conclusion: Few differences in tracheostomy tube placement outcomes were observed for patients with high ventilator settings compared to low ventilator settings. These data demonstrate that patients requiring high ventilator pressures can benefit from tracheostomy tube placement with no additional short‐term risks.